Outcome measures in vitiligo: A narrative review - K.B. Meghana; Anuradha Bishnoi; Davinder Parsad (Pigment International)
Vitiligo disease course being unpredictable in course, it is often difficult to monitor the response to therapy. Though there are many outcome measures, there is a lack of uniformity in reporting these across research papers and clinical trials making it challenging to interpret and compare the results. It is also important to know what matters to the patients in terms of outcome and to include them in outcome assessment. This review consolidates the available validated outcome measures in assessing vitiligo, their advantages, and limitations.